Trajano fundador. el último impulso colonizador del imperio - Javier Bermejo Meléndez; Santiago Robles Esparcia; Juan M. Campos Carrasco (Onoba. Revista de Arqueología y Antigüedad, 2013)
Trajano’s principality is known as one of the periods of maximum brilliance of the Roman empire by the expansionist process that develops to level, economically, politically and territorial. It is in the latter aspect where the labor of the ideal prince supposed one of the last chapters where Rome had a role protagonist in the concert of the ancient world on having obtained his maximum expansion as well as for leading an effervescent period and administrative of territorial reorganization that took equally the creation of numerous colonial, urban and rural foundations, specially in the new conquered territories..